2016
DOI: 10.1016/j.polymer.2016.03.063
|View full text |Cite
|
Sign up to set email alerts
|

High-performance intrinsically microporous dihydroxyl-functionalized triptycene-based polyimide for natural gas separation

Abstract: Please cite this article as: Alaslai N, Ghanem B, Alghunaimi F, Pinnau I, High-performance intrinsically microporous dihydroxyl-functionalized triptycene-based polyimide for natural gas separation, Polymer (2016), doi: 10.1016/j.polymer.2016.03.063. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 56 publications
2
48
0
Order By: Relevance
“…As it is usually found in other polymers, pure CO 2 and CH 4 permeability coefficients of these polyimides decreased with increasing feed pressure up to 15 atm. 27,29,32,33 This preliminarily results indicates that DPPD-MBDAM, DPPD-HFI and DPPD-BAPHF membranes do not present plasticization up to a testing pressure of 15 atm. Fig.…”
Section: Dppd Based Polyimides Gas Transport Propertiesmentioning
confidence: 74%
See 1 more Smart Citation
“…As it is usually found in other polymers, pure CO 2 and CH 4 permeability coefficients of these polyimides decreased with increasing feed pressure up to 15 atm. 27,29,32,33 This preliminarily results indicates that DPPD-MBDAM, DPPD-HFI and DPPD-BAPHF membranes do not present plasticization up to a testing pressure of 15 atm. Fig.…”
Section: Dppd Based Polyimides Gas Transport Propertiesmentioning
confidence: 74%
“…This effect is in agreement with previous reports, which indicate that the introduction of ortho methyl substituted groups in the diamine moieties can increase gas permeability coefficients but they follow the usual trade off since there is a decreased in selectivity. 27,28 Apparent gas diffusion coefficients, D, determined from time lag and apparent gas solubility coefficient S, (calculated from D and P), are presented in Table 6. Also the values of diffusivity selectivity, a(D A /D B ), and solubility selectivity.…”
Section: Dppd Based Polyimides Gas Transport Propertiesmentioning
confidence: 99%
“…Both studies indicated that tailoring the pore surfaces with functionalities brought benefits in CO 2 capture from postcombustion gases. The practices of introducing CO 2 ‐philic groups (e.g., OH, COOH, NH 2 ) onto the pore walls of microporous organic membranes were extensively executed by our researchers …”
Section: Gas Separation With Microporous Organic Membranesmentioning
confidence: 99%
“…The method of pore modulation to improve CO 2 capture efficiency was extended to other microporous organic membranes including crystalline 2D and amorphous 3D ones, the work of which is summarized in Figure . Based on the survey, it can be concluded that introduced surface functionality and small pores contribute significantly to increasing the selectivity, and fully interconnected pores (equivalently by high surface areas) bring a huge enhancement in gas permeability.…”
Section: Gas Separation With Microporous Organic Membranesmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Polyimide is one of the most promising membrane materials for natural gas and biogas separation due to its excellent properties, such as high gas permselectivity, high thermal and chemical resistance, and excellent mechanical properties. [13,14] from triptycene-based diamine DAT and rigid PMDA. The structure of PMDA-DAT and the synthetic procedure was shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%